Enhancing Underhand Volleyball Serve Learning Outcomes Using Rubber Balls in Elementary Schools - Muzaqi, Akhmad; Azizah, Alfiah Rizqi; Sumantri, Riyan Jaya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. This study aims to address the difficulties in underhand serving by improving students’ underhand serve ability through training with rubber balls. The research focuses on fourth-grade students at SD Negeri 1 Sangubanyu during the 2024/2025 academic year in volleyball learning sessions. Material and Methods. This research employs a Classroom Action Research (CAR) methodology, consisting of four stages: planning, implementation, observation, and reflection. Data collection instruments include tests and observations. The study population comprises all 13 fourth-grade students at SD Negeri 1 Sangubanyu, consisting of 9 boys and 4 girls. Data analysis was conducted by reflecting on the observations and evaluations of the learning process, with a quantitative approach providing numerical results. Results. The data analysis revealed an improvement in learning outcomes over two cycles. The mastery learning rate in the first cycle was 14.28%, while in the second cycle, it increased significantly to 71.57%. Conclusion. The findings indicate that utilizing rubber balls in underhand serve training can assist educators in determining effective teaching methods to enhance students’ learning outcomes in volleyball, particularly at the elementary school level. However, the study faced certain limitations, as only 4 students achieved mastery in the initial observation, while 9 students did not. To address this, rubber balls were introduced as an alternative learning aid, making the learning process more engaging and improving students' understanding of the fundamental serve motion. Additionally, time constraints limited the ability to observe long-term progress comprehensively. This study solely focused on underhand serve skills without addressing other aspects of volleyball. The findings serve as a reference for designing more effective and enjoyable learning programs, facilitating students’ comprehension of basic serving techniques. Future researchers are encouraged to further develop this method using other assistive tools, while PE teachers may adopt or modify this approach with various instructional adaptations